Hubs and Pathways - Sepulcre, J.; Sabuncu, M.R.; Goñi, J. (Brain Mapping : An Encyclopedic Reference, 2015)
The brain is organized in modular areas of specific unimodal processing, as well as areas that integrate multimodal and associative information. However, the presence of highly complex neuronal interactions has limited our abilities to understand how brain systems assemble together. In recent years, the development of structural and functional neuroimaging techniques combined with the emergence of network analytic methods, such as graph theoretical tools, has revealed key properties about segregation and integration centers of the human brain.